1997
DOI: 10.1177/070674379704200205
|View full text |Cite
|
Sign up to set email alerts
|

The History of the Psychopharmacology of Schizophrenia

Abstract: Close collaboration between basic neuroscience and careful and informed clinical practice are likely to lead to continued progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 64 publications
0
50
0
5
Order By: Relevance
“…[20][21][22][23] Following the introduction of chlorpromazine and the first neuroleptics, EPS were thought to be a prerequisite for antipsychotic efficacy. 2,24 Clozapine and other SGAs violated this principle by having antipsychotic efficacy with little or no EPS, 3 hence the term 'atypical' antipsychotic. Subsequently, SGAs were observed to have an increased risk of metabolic side effects.…”
Section: The Relationship Between the Comparative Effectiveness And Mmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23] Following the introduction of chlorpromazine and the first neuroleptics, EPS were thought to be a prerequisite for antipsychotic efficacy. 2,24 Clozapine and other SGAs violated this principle by having antipsychotic efficacy with little or no EPS, 3 hence the term 'atypical' antipsychotic. Subsequently, SGAs were observed to have an increased risk of metabolic side effects.…”
Section: The Relationship Between the Comparative Effectiveness And Mmentioning
confidence: 99%
“…1 Antipsychotic drugs have been the primary treatment for approximately half of a century, beginning with the discovery and introduction of chlorpromazine. 2 However, despite the extensive use and study of these agents, questions remain regarding their exact mechanism of action. 3 Much of the study to date has focused on the receptor profiles of these medications.…”
Section: Introductionmentioning
confidence: 99%
“…Mn has a role in thyroxine synthesis and thyroxine effects G6PD enzyme synthesis in a similar way. There is also a relationship between Mn and dopamine and it has been reported that antipsychotic drugs chelate body Mn (16,36).…”
Section: Discussionmentioning
confidence: 99%
“…These assumed remedies were not based on sound pathological data, but nevertheless reflected the predominant somatic perception of schizophrenia at this time. Because the etiological nature of the disorder was entirely unknown, extant treatments, including insulin coma therapy (Sakel, 1937;Jones, 2000) and metrazol therapy (Lehmann & Ban, 1997), were administered on a trial and error basis; they were largely unsuccessful and ultimately abandoned (Lehmann & Ban, 1997). Although the somatic perception of schizophrenia dominated psychiatric thinking during this time, psychoanalytic theory also had a significant impact on the thinking and, in certain places, on the treatment of such patients.…”
Section: Schizophrenia Circa 1930mentioning
confidence: 98%